The influence of digital competence and employee performance on the quality of electronic services - Elli Marlina; Rima Elya Dasuki; Ucu Nurwati (Jurnal Mantik, 2023)
This research aims to determine the influence of digital competence and employee performance on the quality of electronic services at the Unpad FISIP Library by students as service users. This research uses a quantitative approach and descriptive analysis methods. The population in this research is all FISIP Unpad students who use the electronic services of the FISIP Unpad Library in 2022-2023 with a population of 1,355 people and a sample of 100 people. The sample size sampling technique in this study used a nonprobability sampling technique with quota sampling rules. The data collection technique in this research uses a questionnaire with a Likert scale measurement. The analysis in this research uses classical assumption tests, multiple regression analysis, coefficient of determination analysis, and partial or simultaneous hypothesis testing. The results of the research show that the digital competence and performance of the Unpad FISIP Library librarian employees are rated as very high or very qualified, while the quality of the Unpad FISIP Library's electronic services is rated as high/qualified. The results of partial hypothesis testing show that digital competence and employee performance have a positive and significant effect on the quality of electronic services. The results of simultaneous hypothesis testing show that digital competence and employee performance have a positive and significant effect on the quality of electronic services